Video game design : principles and practices from the ground up - Salmond, Michael (London : Fairchild Books, an imprint of Bloomsbury Publishing Plc, 2016)
Video game design" is a visual introduction to integrating core design essentials, such as critical analysis, mechanics and aesthetics, prototyping, level design, into game design. Using a raft of examples from a diverse range of leading international creatives and award-winning studios, this is a must-have guide for budding game designers. Industry perspectives from game industry professionals provide fascinating insights into this creative field, and each chapter concludes with a workshop project to help you put what you've learned into practice to plan and develop your own games.With over 200 images from some of the best-selling, most creative games of the last 30 years, this is an essential introduction to industry practice, helping readers develop practical skills for video game creation. This book is for those seeking a career making video games as part of a studio, small team or as an independent creator. It will guide you from understanding how games engage, entertain and communicate with their audience and take you on a journey as a designer towards creating your own video game experiences.
-- So you want to be a video game designer? -- World building -- Video game analysis -- Understanding the motivations for play -- Video games are event-driven experiences -- Planning, preparation, and play- testing -- Character design -- Bringing it all together -- The engagement engine -- Keeping them playing -- Interface design and audio design -- Monetization, copyright, and intellectual property.
Includes bibliographical references (page 257) and index.
Keywords: Video games -- Design; Computer games -- Design; Video games -- Authorship